Creating healthy workplaces : stress reduction, improved well-being, and organizational effectiveness. - Biron, Caroline (Psychological and behavioral aspects of risk series., 2014)
Creating Healthy Workplaces includes interventions that relate the efforts undertaken by researchers and organizations to reduce stress and improve the mental and physical health of employees through positive change initiatives. Those working in the field of occupational stress have received criticism that too much emphasis has been placed on negative issues and that positive initiatives have been largely ignored. This book delves into both the positive and the stress fields and compares the types of interventions each entail. Some of the interventions described target individuals and their at.